perkembangan Motorik Kasar Melalui Permainan Lompat Tali Pada Anak Kelompok A Di Lembaga Ra Al-Istiqomah Gsi - Siti Agustiani; Rini Kurniawati; Siti Rohmah; Santy Hataul; Sary Rina Naruvita; Agus Sudarya (Publikasi Indonesia, 2022)
Good and correct gross motor stimulation can lead children to achieve optimal development. Unfortunately, many children whose gross motor skills have not developed optimally, this is because in learning teachers tend to use the lecture method so that children are less involved and do not practice directly to develop gross motor skills. Through the game of jumping rope, in addition to training cooperation and understanding, jumping rope will also demand the child's brain and body to maximize performance and movement. So that it will make good and perfect growth and development between intelligence and movement in the face of obstacles and problems. The method used in this research is the classroom action research method. The subjects involved in this study were 23 students of group A at RA Al-Istiqomah GSI, Griya Serdang Indah B, Margatani Village, Kramatwatu District, Serang Regency, Banten. The final result of the study showed that 96% of children developed very well in gross motor skills. Through the game of jumping rope, children's gross motor skills are well stimulated.